2007
DOI: 10.21273/hortsci.42.2.232
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Levels in Nine Lettuce (Lactuca sativa) Cultivars: Influence of Planting Date and Relations among Analytic, Instrumented, and Visual Assessments of Color

Abstract: Leaf samples collected from field plots of nine lettuce cultivars established in the early (ES) and late (LS) summer of 2002 and 2003 in Celeryville, Ohio, were subjected to spectrophotometric measurement of anthocyanin concentrations or color analysis based on colorimeter and spectroradiometer readings and human panelist ratings. Interactions among year (Y), transplanting date (TD), and cultivar (C) main effects for anthocyanin concentration were significant as a result of shifts in response magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 33 publications
8
51
1
Order By: Relevance
“…Panelists, however, could not determine red color in a cultivar with a low anthocyanin level. Similarly, we have detected anthocyanin through hyperspectral analysis in the leaf samples with the ‘no red’ color rating, confirming that the threshold level of anthocyanin needed for the detection by visual observation is higher than is the actual level of anthocyanin in some lettuces (Gazula et al, 2007). …”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Panelists, however, could not determine red color in a cultivar with a low anthocyanin level. Similarly, we have detected anthocyanin through hyperspectral analysis in the leaf samples with the ‘no red’ color rating, confirming that the threshold level of anthocyanin needed for the detection by visual observation is higher than is the actual level of anthocyanin in some lettuces (Gazula et al, 2007). …”
Section: Discussionsupporting
confidence: 71%
“…Hence, the breeders selecting for dark red color (high RAC) may consider temporarily subjecting lettuce plants to low temperatures where differences among genotypes are likely to be more pronounced (assuming that the pattern of changes in pigments is the same as in our study). These results are somewhat unexpected, because several previous studies reported that low temperatures lead to increased anthocyanin production in lettuce (Gazula et al, 2005, 2007; Boo et al, 2011; Chon et al, 2012; Becker et al, 2014a). However, when the regulation of anthocyanin biosynthesis [quantified as cyanidin-3- O -( 6 ″-malonyl)-glucoside] was compared in three cultivars, a substantial difference in their response to varying temperatures was detected.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Ultimately, the quality of herbs is mainly defined in terms of consumer acceptability, which is mostly based on appearance such as freshness, uniformity of size and shape, right maturity, right colour, freedom from defects (such as rot, physical damage and yellowing or wilting), flavour and aroma [5]. The quantity and distribution of chlorophylls contribute significantly to the leaf colour and product appeal [6]. Postharvest overall quality, phytochemical composition and storage life are influenced by the environment and cultural practices; these include seasonal growing temperatures, light conditions, the amount of rainfall and irrigation, mineral nutritional status and fertilisation, pest management, and maturity at harvest time.…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant phenolics in lettuce vary amongst varieties due to growing practices, processing and storage conditions (Baur, Klaiber, Koblo, & Carle, 2004). Currently, red lettuce is popular in salad mixes due to its anthocyanin content that contributes to the higher value it fetches compared to the green lettuce (Gazula, Kleinhenz, Scheerens, & Ling, 2007). The increased demand of fresh vegetables associated with health benefits has led to an increase in the quality, quantity and variety of produce available to the consumer.…”
Section: Introductionmentioning
confidence: 99%